Nonapeptides and the Evolution of Social Group Sizes in Birds - James L. Goodson; Marcy A. Kingsbury (Frontiers Media S.A., 2011)
Species-typical patterns of grouping have profound impacts on many aspects of physiology and behavior. However, prior to our recent studies in estrildid finches, neural mechanisms that titrate species-typical group size preferences, independent of other aspects of social organization (e.g., mating system and parental care), have been wholly unexplored, likely because species-typical group size is typically confounded with other aspects of behavior and biology. An additional complication is that components of social organization are evolutionarily labile and prone to repeated divergence and convergence. Hence, we cannot assume that convergence in social structure has been produced by convergent modifications to the same neural characters, and thus any comparative approach to grouping must include not only species that differ in their species-typical group sizes, but also species that exhibit convergent evolution in this aspect of social organization. Using five estrildid finch species that differ selectively in grouping (all biparental and monogamous) we have demonstrated that neural motivational systems evolve in predictable ways in relation to species-typical group sizes, including convergence in two highly gregarious species and convergence in two relatively asocial, territorial species. These systems include nonapeptide (vasotocin and mesotocin) circuits that encode the valence of social stimuli (positive-negative), titrate group-size preferences, and modulate anxiety-like behaviors. Nonapeptide systems exhibit functional and anatomical properties that are biased towards gregarious species, and experimental reductions of nonapeptide signaling by receptor antagonism and antisense oligonucleotides significantly decrease preferred group sizes in the gregarious zebra finch. Combined, these findings suggest that selection on species-typical group size may reliably target the same neural motivation systems when a given social structure evolves independently.